Uji Nilai Kalor Oli Bekas Sepeda Motor Sebagai Bahan Bakar Mesin Diesel Dongfeng R175 - Arief Rachman Widyanto; Aryo Sasmita; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The production laboratory of the Department of Mechanical Engineering Riau University, has modified the diesel engine used as a used oil fueled generator, the problem is that the emission feasibility test has not been carried out. The purpose of this study was to determine the calorific value of used motorcycle oil and compare it with dexlite and to measure this calorific value using a bomb calorimeter. Keywords: Calorific value, Diesel engine, Used motorcycle oil, Fuel.